Combinatorial screening of dysprosium-magnesium-zinc alloys for bioresorptive implants. (10th December 2020) - Recktenwald, Dominik; Mardare, Cezarina Cela; Mardare, Andrei Ionut; Jinga, Luiza-Izabela; Socol, Gabriel; Hassel, Achim Walter
Highlights: Small Dy additions (< 0.5 at.%) lead to thin film amorphization in Mg-Zn alloys. Higher Dy additions (> 0.5 at.%) lead to enhanced surface morphology features. Dy-Mg-Zn alloys show superior corrosion resistance up to 20 at.% Zn. Estimated corrosion rates of 3 mm y −1 and lower could be reached. Zn dissolution is strongly decreased due to passive corrosion product formation. Abstract: A thin film dysprosium-magnesium-zinc combinatorial library has been deposited using a thermal co-evaporation technique. Scanning EDX, XRD, SEM and XPS were used to investigate the structure, surface morphology and species present. The entire library was found to be amorphous and morphological changes were visible by minor additions of Dy (approximately 1 at.%) and medium to high Zn contents (> 20 at.%). Open circuit potential, electrochemical impedance spectroscopy and potentiodynamic polarization measurements revealed a higher corrosion resistance for Zn-poor alloys (<15 at.%), which was demonstrated by downstream ICP-OES analytics. Electrochemical measurements on Zn-rich alloys evidenced Mg release of up to 200 ng s −1 cm −2 . This makes them unsuitable for biomedical applications due to the high H2 gas evolution. A low Dy content of up to 0.5 at.% was shown to further increase the corrosion resistance with Mg release rates of less than 5 ng s −1 cm −2 . Alloys in this region are therefore considered valuable candidates for biomedical implants. The study showed best electrochemical properties, thus the most promising alloy, at a composition range of 0.5 at.% Dy 15.0 at.% Zn and Mg as balance. Graphical abstract: Image, graphical abstract